Linking family farming to endoparasites implicated in public health: A review of current health discussions - Fitte, Bruno (2023)
Family farming is essential in relation to food security, generation of employment, mitigation of poverty and conservation of biodiversity. Many governments have considered it a sector of indigence and degradation, adopting an agro-export model, which contributed to deepening inequality. Since 2000 decade, many countries started to include family farmers in their agenda. Only a few surveys have linked family farming to endoparasites, including zoonotic species. The aim of this paper was to review the records available of helminths, focusing on those with sanitary implication, and the protozoa Toxoplasma gondii, Neospora caninum and Cryptosporidium spp. Collection of data based upon literature available. Helminths with sanitary risk recorded were Ascaris spp., Capillaria spp., Enterobius vermicularis, Fasciola spp., Hymenolepis spp., Schistosoma spp., Taenia spp., Toxocara spp. and Trichuris spp., with prevalence values 0.1 to 95.8%. Three protozoa taxa were recorded, with prevalence values 1.4 to 70%. There is a common concern regarding the sanitary conditions that prevail in family farming system. It is necessary to create the conditions for family farmers to have access to information and education on safe food practices. Governments are called to correct this situation, promoting social integration and economic development, taking into account the particularities of each area.